Standardization Of Egg Randang Recipes In Nagari Mungka, Payakumbuh City - Della Regina Agustin; Wirnelis Syarif (Universitas Negeri Padang, 2021)
The purpose of this study is to standardize the recipe for egg randang in Nagari Mungka,Payakumbuh City which includes the use of ingredients, spices, tools, processing techniques and analyzing quality in terms of shape,color,smell,texture and taste. This research is motivated by differences in the use of basic spices,processing techniques and the dosage of ingredients in the processing of egg randang so that the resulting quality is different. This type of research is a mixed method (combination of qualitative and quantitative research). Sources of qualitative data obtained from 10 people who are expert in making randang eggs and sources of quantitative data obtained from 10 trained panelists of community who know about egg randang and the 5 panelists limited culinary art of Padang State University. Based on the research results, it is find that the standard recipe for egg randang includes the main ingredients,spices,tools,processing techniques and quality. The organoleptic test of the standard recipe for egg randang resulted is shape of egg randang (quite parallelogram), color of egg randang dadak (blackish brown),color of egg randang (brownish yellow),smell (fragrant randang),texture of egg randang dadak (quite dry),texture of egg randang (quite crisp and quite brittle),and (savory) taste. Keyword: Standardization,Egg Randang,Mungka